Assessment of Bleaching Treatments With The Ohip-14 Survey - Derya Gürsel Sürmelioğlu; Zeyneb Merve Özdemir (Current Research in Dental Sciences, 2024)
Objective: The aim of this study is to evaluate the effect of teeth bleaching on oral health and quality of life (OHIP-14) in adults who have undergone office bleaching treatment.Material and Methods: One hundred patients who applied to our clinic for bleaching treatment between 2016-2021 and underwent bleaching treatment with Opalescence Boost 40% PF were included in the study. Pre-treatment color determination is routinely done for each patient in the clinic. They were divided into four different groups as follow-up patients in 3rd month for Group 1, 6th month for Group 2, 1st year for Group 3, and 2nd year follow-up patients for Group 4 (n=25). Shade guide unit (ΔSGU) values were calculated for the patients using the Vita Classic color scale. In addition, the OHIP-14 questionnaire was applied to each patient to evaluate the effect of bleaching on oral health and quality of life. Wilcoxon and Kruskal-Wallis tests were performed at P.05). In terms of color change, no significant difference compared to baseline levels with the measurements made at the 3rd, 6th months, and 1st and 2nd years (P.>05, =0.81).Conclusion: After the bleaching treatment, the color remained stable for two years. However, a positive psychosocial effect and improved self-perception occurred in the patients.Key Words: Bleaching treatment, OHIP-14, quality of life